Financing Water and Sanitation Projects : The Unique Risks - Haarmeyer, David; Mody, Ashoka (World Bank, Washington, DC, 2012)
A project finance structure allows water projects with attractive cash flows and risk profiles to secure long-term private capital. But even in industrial countries the credit strength of off-taking municipal governments and the sector's traditional monopoly structure expose lenders to potentially significant credit, regulatory, and political risks. These risks, combined with the sunk, highly specific, and non-redeployable nature of water infrastructure investments, mean that lenders and investors are vulnerable to opportunistic contracting problems and expropriation. Reviewing some recent innovative water and sanitation projects, the authors show that private capital participation on a limited recourse or nonrecourse basis has required support by third parties such as multilaterals and federal government agencies to absorb noncommercial risks.